Penyuluhan Hukum Mengenai Ancaman Pidana Poligami Tanpa Izin Istri Sah - Jaidun, Jaidun (Jurnal Pengabdian Ahmad Yani, 2023)
The aim to be achieved in community service activities with the theme "Legal education regarding the criminal threat of polygamy without a permit" is to support higher education programs as educational centers in providing and increasing knowledge to the community regarding the potential for legal problems in the future, if there are parties ( husband) who engages in polygamy without written permission from the first wife, apart from that in order to disseminate information to the community and family (as part of community members) about the dangers and legal risks and the risk of quarrels in the household which can lead to divorce and going to prison. This community service activity is carried out in two stages, namely, preparation and implementation of the core program. Community Service (PPM) through legal counseling, providing knowledge to participants, especially regarding polygamy according to Islamic teachings, the requirements for polygamy according to the provisions of Law number 1 of 1974, the risk of domestic conflict, if you carry out polygamy without written permission from first wife and the potential for criminal problems related to domestic life. The material presented can be received, digested and understood by participants well.